Rosai-Dorfman disease affecting the maxilla - Thaís Gimenez Miniello; Juliane Piragine Araujo; Norberto Nobuo Sugaya; Fernando Melhem Elias; Oslei Paes de Almeida; Fabio Abreu Alves (University of São Paulo, 2016)
Rosai-Dorfman disease (RDD), formerly called sinus histiocytosis with massive lymphadenopathy, is a non-neoplastic proliferative histiocytic disorder with behavior ranging from highly aggressive to spontaneous remission. Although the lymph nodes are more commonly involved, any organ can be affected. This study aimed to describe the features and the follow-up of a case of extranodal RDD. Our patient was a 39-year-old woman who was referred with an 11-month history of pain in the right maxilla. On clinical examination, some upper right teeth presented full mobility with normal appearance of the surrounding gingiva. Radiographic exams showed an extensive bone reabsorption and maxillary sinus filled with homogeneous tissue, which sometimes showed polypoid formation. An incisional biopsy demonstrated a diffuse inflammatory infiltrate rich in foamy histiocytes displaying lymphocytes emperipolesis. Immunohistochemistry showed positivity for CD68 and S-100, and negativity for CD3, CD20, and CD30. Such features were consistent with the RDD diagnosis. The patient was referred to a hematologist and corticotherapy was administrated for 6 months. RDD is an uncommon disease that rarely affects the maxilla. In the present case, the treatment was conservative, and the patient is currently asymptomatic after 5 years of follow-up